Facile Preparation of Acid-Resistant Polyester Fabrics With Organic/Inorganic Nanocomposites. (April 2017) - Wang, Helan; Xu, Lihui; Song, Xiaoxiao; Cai, Zaisheng
A facile method to prepare acid-resistant fabric with fluoropolymer/silicon dioxide (SiO2 ) nanocomposite is presented in this study. Response surface methodology (RSM) was employed to understand the influence factors of the optimized protocol for the acid-resistant fabric. During the preparation process, the effect level of the factors was agent concentration > curing temperature > curing time. The treated fabric showed a remarkable acid repellency, having a contact angle greater than 137°. Additionally, when the fabric was immersed in 80% sulfuric acid (H2 SO4 ) for 5 min, it had a 4% and 9% decrease in breaking force in the warp and weft directions, respectively. We believe that the acid-resistant fabric developed as part of this study will receive more opportunities to the application of protective clothing, and the regression analysis provided by RSM can be extended into other procedures for textile preparation.